ANALISIS KEBISINGAN BEBERAPA RUANG TERBUKA HIJAU DI KOTA MANADO - Nastasia Irene Potoboda; Josephus Kalangi; Fabiola B. Saroinsong (Universitas Sam Ratulangi, 2021)
ABSTRACTNOISE ANALYSIS GREEN OPEN SPACE IN MANADO CITYThis study aims to analyze the noise leve in several green open spaces in the city of Manado.This research was conducted in march 2020 in three locations, namely the UNSRAT field, theKONI field, and Jln.Piere Tendean-Ahmad Yani,Manado city, North Sulawesi. This study uses apurposive sampling method in determining the sampling point by means of measurements usinga sound level meter (SLM) and the data is processed by surfer 11 software. The results of thenoise level research for UNSRAT Field 40-70 dB(A), KONI Field 47-79 dB(A), and Jln.PiereTendean-Ahmad Yani 50-95 dB(A). From the results of the analysis of existing noise levels, itshows that the location with the highest noise level is Jln.Piere Tendean-Ahmad Yani which areincluded in the green open space area which are included in the green open space area whichonly reaches 71 dB(A) and 79 dB(A) the highest.Keywords: Noise, Green open space, and Manado City.